ПЕДАГОГІКА СОЦІАЛІЗАЦІЇ: ОСОБЛИВОСТІ ПАТРІОТИЧНОГО ВИХОВАННЯ ДІТЕЙ ДОШКІЛЬНОГО ВІКУ - Рогальська-Яблонська, Інна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті обґрунтовано особливе значення правової соціалізації особистості та висвітлено особливості патріотичного виховання дітей. Підкреслено, що основою сучасного патріотичного виховання дітей є ціннісні орієнтації, які з віком і дорослішанням дитини змінюються, стають більш стійкими, умотивованими. Запропоновано методи і засоби донесення до свідомості дітей первинних уявлень про права та обов’язки кожної людини. В статье обосновано важное значение правовой социализации и раскрыты особенности патриотического воспитания детей. Подчеркнуто, что основой современного патриотического воспитания являются ценностные ориентации, которые с возрастом и взрослением ребенка изменяются. Становятся более стойкими и мотивированными. Предложены методы и средства донесения в сознание детей первичных представлений про права и обязанности каждого человека. In the article the special importance of legal socialization and the peculiarities of patriotic education of children. Emphasized that the purpose and objectives of the patriotic education of the individual in general, determined the public interest and directed to the formation of a citizen state, harmonious development, equitable, nationally conscious individual. It is emphasized that the foundation of modern patriotic education of children is the values, that with age and maturation child changing, becoming more resilient, motivated. The author notes that collaborating with a culture in which accumulated symbols, customs, skills, values, ideas and traditions of previous generations, mastering them, the child learns the way of social and cultural life. The importance given to this traditional pedagogy, because for centuries the Ukrainian people and concluded accumulated in their property information layers educational experience, vision, values, convictions for the purpose of its preservation. The methods and means of informing the minds of children of primary notions of rights and duties of each person.